Pengaruh Social Media Marketing, Event Sponsorship, Flash Sale, Dan Packaging Terhadap Keputusan Pembelian Pada Produk Pinkflash - Nisa, Firda Hanikati; Rizal, Mohammad; Utama, Satria Putra (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The importance of effective marketing strategies and innovation in the beauty industry which continues to change and compete rapidly means that top brands must always follow the latest trends and continue to innovate to remain relevant in an increasingly dynamic market. This study identifies the relationship between proactive marketing strategies and purchasing decisions. consumer. This research aims to analyze and describe the influence of Social Media Marketing, Event Sponsorship, Flash Sale, and Packaging on Purchase Decisions for Pinkflsah Products in Malang City. The population in this study were residents of Malang City with a sample size of 100 people, using the Slovin formula and using the proportional sampling method. The data collection technique used in this research was by distributing questionnaires via Google Form. Research data uses SPSS 25. The results of this research show that simultaneously Social Media Marketing, Event Sponsorship, Event Sponsorship, Flash Sale, and Packaging have a significant effect on Purchasing Decisions. Social Media Marketing has a significant effect on Purchasing Decisions, Event Sponsorship has no significant effect on Purchasing Decisions, Flash Sale has no significant effect on Purchasing Decisions, Packaging has a significant effect on Purchasing Decisions Keywords: Social Media Marketing, Event Sponsorship, Flash Sale, Packaging, Purchasing Decisions.